Analisis Tata Kelola Dana Desa dan Alokasi Dana Desa, dan Pengaruhnya Terhadap Penanggulangan Kemiskinan di Kabupaten Bogor - Arif Fadilla; Gamal Sinurat; Jayadin Jayadin (Ekonomikawan: Jurnal Ilmu Ekonomi dan Studi Pembangunan, 2023)
National development seeks to improve people's welfare, one of which is seen from the poverty rate indicator. One of the government's priorities in reducing poverty in rural areas is the distribution of Village Funds since the issuance of the Law. No. 6 of 2014 concerning Villages. This Village Fund disbursement policy has been started since 2015 until now and many studies related to the effectiveness of Village Funds for poverty alleviation. An interesting empirical fact is that Bogor Regency is geographically very close to the State Capital, Jakarta, with the largest number of poor people in Indonesia at the district and city levels. The purpose of this study is to examine the impact of Village Funds on poverty rates in Bogor Regency, as well as the role of Village Government in poverty alleviation. With this approach it was found that for Bogor Regency the Village Fund Variable had a small negative correlation to the reduction in the poverty rate, while the Village Fund Allocation had a very strong negative correlation to poverty.